The Role Physical Activity in the Prevention and Control of Diabetes Mellitus – A Narrative Review - Warych, Wiktor; Wojciechowska, Karolina; Zajkowska, Izabela; Zabrocka, Patrycja; Martowska, Julia; Choroszewska, Ewelina; Baran, Julia (Quality in Sport, 2026)
Diabetes mellitus is one of the most prevalent chronic non-communicable diseases worldwide and constitutes a major public health challenge due to its growing incidence, high morbidity and mortality, and substantial socioeconomic burden. Insufficient physical activity has been identified as a key modifiable risk factor contributing to the development and progression of diabetes, particularly type 2 diabetes mellitus, but also influencing metabolic control and complication risk in type 1 diabetes mellitus. The present narrative review summarizes current evidence regarding the role of physical activity in the prevention and control of diabetes mellitus. A comprehensive analysis of peer-reviewed original studies, systematic reviews, and clinical guidelines was conducted. The available evidence demonstrates that regular physical activity significantly reduces the risk of developing type 2 diabetes, improves glycemic control and insulin sensitivity in individuals with established diabetes, and exerts beneficial effects on cardiovascular fitness, body composition, inflammatory status, and oxidative stress. Furthermore, physical activity has been shown to attenuate the progression of both microvascular and macrovascular complications. These findings support the inclusion of structured physical activity as a fundamental component of diabetes prevention strategies and routine clinical management. Background:Diabetes mellitus is a chronic metabolic disorder characterized by persistent hyperglycemia resulting from impaired insulin secretion, impaired insulin action, or a combination of both. The global prevalence of diabetes has increased markedly over recent decades, driven by population aging, urbanization, obesity, sedentary lifestyles, and unfavorable dietary patterns. Type 2 diabetes mellitus accounts for more than 90% of all cases and is strongly associated with modifiable lifestyle factors, whereas type 1 diabetes mellitus is primarily autoimmune in origin but similarly associated with elevated cardiovascular risk and reduced life expectancy. Physical inactivity has emerged as an independent risk factor for insulin resistance, impaired glucose tolerance, cardiovascular disease, and premature mortality. Skeletal muscle, the primary site of insulin-mediated glucose uptake, plays a central role in glucose homeostasis and represents a key target for exercise-induced metabolic adaptations. Regular physical activity improves glucose uptake through both insulin-dependent and insulin-independent mechanisms and induces favorable changes in mitochondrial function, lipid metabolism, inflammatory signaling, and antioxidant defense systems. Consequently, increasing attention has been directed toward physical activity as a cost-effective and scalable intervention for diabetes prevention and long-term disease control. Aim:The aim of this review was to evaluate the role of physical activity in the prevention of diabetes mellitus and in the metabolic control and complication management of individuals with established type 1 and type 2 diabetes mellitus. Material and Methods:This narrative review was based on an analysis of peer-reviewed scientific literature, including original research articles, randomized controlled trials, observational studies, systematic reviews, and expert consensus statements. The included publications focused on epidemiology, pathophysiological mechanisms, clinical outcomes, and exercise prescription related to physical activity in diabetes prevention and management. Results:The reviewed evidence consistently demonstrates that regular physical activity is associated with a substantial reduction in the risk of developing type 2 diabetes mellitus. In individuals with established diabetes, physical activity improves glycemic control, insulin sensitivity, lipid profile, blood pressure, and cardiorespiratory fitness. Both aerobic and resistance exercise modalities provide metabolic benefits, with combined training programs yielding the most pronounced effects. Additionally, regular physical activity reduces markers of systemic inflammation and oxidative stress and attenuates the progression of diabetes-related microvascular and macrovascular complications. Conclusions:Physical activity represents a fundamental, evidence-based component of diabetes prevention and management. Its regular incorporation into lifestyle interventions and clinical care is essential for improving metabolic control, reducing complication risk, and enhancing long-term health outcomes in individuals at risk of or living with diabetes mellitus.